(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
Today, when carrying out reforms for the development of Uzbek society, full opportunities and conditions are created for the fulfillment of the tasks set for Uzbek linguistics, purposeful research work is being carried out on the issue of a comprehensive study of the Uzbek language. At the same time, the study of the features of Uzbek dialects, based on the theoretical foundations of areal linguistic research, is defined as one of the priority areas in the historical-comparative and ethnolinguistic aspects. This area consists of imperfect, simple descriptive and illustrative aspects, uncertain places need to be studied and filled in based on new views, from a mental point of view. Research using areal-typological and areal-linguistic methods, which gave Mahmud Kashgar in the Turkic languages the starting point of any linguistic theory and concepts, the study of dialects, their specific features, remains one of the important issues today. The emergence of areal linguistics has opened up ample opportunities for assessing new problems and concepts in the field of dialectology, for their solution in a new way. Based on the theoretical basis of dialect and slang areas in the holistic study of the language system, the fact that historical-comparative and ethnological studies are identified as one of the priority areas imposes new responsibilities on Uzbek linguistics and Uzbek linguists. The article gives an idea of the peculiarities of the Namangan Kypchak and Karluk dialects, the historical genesis of the vowel system, the problems of their distribution and use. The phonetic-phonological linguistic character of the dialect is a comparative-historical reflection of the processes of events of properties and patterns. In turn, the article also describes opinions about the events of the umlaut in the Turkic dialects of singharmonism and the Karluk dialects in the Kipchak dialects related to vowels in the Turkic languages.